Exogenous Pulmonary Surfactant as a Vehicle for Antimicrobials: Assessment of Surfactant-Antibacterial Interactions In Vitro - Alexei Birkun (Scientifica)
Owing to its unique surface-active properties, an exogenous pulmonary surfactant may become a promising drug delivery agent, in particular, acting as a vehicle for antibiotics in topical treatment of pneumonia. The purpose of this study was to assess a mutual influence of natural surfactant preparation and three antibiotics (amikacin, cefepime, and colistimethate sodium) in vitro and to identify appropriate combination(s) for subsequent in vivo investigations of experimental surfactant/antibiotic mixtures. Influence of antibiotics on surface-active properties of exogenous surfactant was assessed using the modified Pattle method. Effects of exogenous surfactant on antibacterial activity of antimicrobials against Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa were evaluated using conventional microbiologic procedures. Addition of amikacin or cefepime to surfactant had no significant influence on surface-active properties of the latter. Obvious reduction of surface-active properties was confirmed for surfactant/colistimethate composition. When suspended with antibiotics, surfactant either had no impact on their antimicrobial activity (amikacin) or exerted mild to moderate influence (reduction of cefepime bactericidal activity and increase of colistimethate bacteriostatic activity against S. aureus and P. aeruginosa). Considering favorable compatibility profile, the surfactant/amikacin combination is advisable for subsequent investigation of joint surfactant/antibacterial therapy in animals with bacterial pneumonia.